A novel ultrasonic technique for the study of refrigeration and fermentation effect of coconut water (International Journal of Food and Nutritional Sciences, 2022)
A continuous study is performed to analysethe fermented as well as refrigerated effect of coconut water using ultrasonic parameters namely adiabatic compressibility (β_s) and specific acoustic impedance (Z_A) by employing its thermal variations. This technique – Thermo - Acoustic Analysis (TAA) has been done to refrigerated, air fermented and yeast fermented samples of coconut water to study its physical properties using ultrasonic parameters. The study reveals that physical properties are unaltered in refrigerated samples whereas a relative shift in the parameters occurs in fermented samples which are greater for yeast fermented samples.